2013
DOI: 10.1021/jp312576v
|View full text |Cite
|
Sign up to set email alerts
|

Solution NMR and Computational Methods for Understanding Protein Allostery

Abstract: Allosterism is an essential biological regulatory mechanism. In enzymes, allosteric regulation results in an activation or inhibition of catalytic turnover. The mechanisms by which this is accomplished are unclear and vary significantly depending on the enzyme. It is commonly the case that a metabolite binds to the enzyme at a site distant from the catalytic site yet its binding is coupled to and sensed by the active site. This coupling can manifest in changes in structure, dynamics, or both at the active site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
48
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 64 publications
4
48
1
Order By: Relevance
“…As such, experimental and computational strategies to identify low-probability states are critical. In addition to NMR 55,9295 , fundamental progress has been made in detecting such low-populated states combining other structural biology techniques 51,96 , with at least one X-ray crystallography study corroborating the states detected by NMR 51 . The ability to observe alternative conformations masked by the cryogenic temperatures typically used in structural analysis 51,97 , and to resolve, using ensemble refinement, multiple states from crystal data collected at room temperature 98 , reveal a much richer dynamic picture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As such, experimental and computational strategies to identify low-probability states are critical. In addition to NMR 55,9295 , fundamental progress has been made in detecting such low-populated states combining other structural biology techniques 51,96 , with at least one X-ray crystallography study corroborating the states detected by NMR 51 . The ability to observe alternative conformations masked by the cryogenic temperatures typically used in structural analysis 51,97 , and to resolve, using ensemble refinement, multiple states from crystal data collected at room temperature 98 , reveal a much richer dynamic picture.…”
Section: Discussionmentioning
confidence: 99%
“…The term ‘dynamic allostery’ has even found its way into the modern lexicon, ostensibly to describe the role of entropy in the thermodynamics of allostery, although unfortunately it is often conflated with motions between relevant ensembles. However, with the development of NMR techniques to study allosteric protein systems at a site-resolved level, both aspects of the role of motion in transitions between functional states are becoming illuminated 5155 .…”
Section: From Structures To Ensemblesmentioning
confidence: 99%
“…(Lipchock et al, 2009, 2010) A subsequent computational analysis further demonstrated that molecular motions were involved in propagating allosteric information from the PRFAR binding site to the HisF/HisH interface. (Manley et al, 2013; Rivalta et al, 2012) In particular, communication among dynamic clusters determined from network analysis is more robust when PRFAR is bound compared to the loosely connected communities of the apo enzyme. The network of dynamic residues identified in NMR and computational studies represents a putative allosteric pathway involving α-helices within HisF ( f α2, f α3) and HisH ( h α1) 1 , extending from the PRFAR binding site to the dimer interface and beyond to the HisH glutaminase active site.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have advanced these studies and demonstrated that activation of IGPS is dependent on the ability of allosteric effectors to stimulate domainwide motions in the HisF subunit and ligands that induce greater motion within the central (αβ) 8 barrel are more effective activators of glutaminase chemistry (22). NMR and computational community network studies proposed an optimal allosteric pathway through networks of HisF amino acid residues that link the PRFAR binding site and adjacent flexible loop 1 to residues comprising a central hydrophobic cluster essential for catalysis, as well as salt bridge residues at the dimer interface (25,26). These previous results suggest important amino acids in each community that, upon mutation, should disrupt the IGPS allosteric network.…”
mentioning
confidence: 99%